VIRULENCE FACTORS AND SUSCEPTIBILITY PATTERN OF ISOLATES OF TRIBE PROTEAE FROM CLINICAL SAMPLES IN A TERTIARY CARE HOSPITAL - S.S.M.UMAMAGESWARI; M. JEYA; J.PERUMAL (International Journal of Pharma and Bio Sciences, 2013)
A total of 172 bacterial isolates with the split up of Proteus (128), Morganella (27) and Providencia (17) were isolated from various clinical specimens. Maximum isolates were obtained from urine 86 (50%) and pus 73 (42.4%). Proteus and related genera are 97% sensitive to carbapenem groups of antibiotics, 80 - 90% sensitive to piperacillin /tazobactam, amikacin and gentamycin and only 50% sensitive to all other cephalosporin and ciprofloxacin. Haemagglutination was shown by 122 (71%) strains, Hemolysin production in 140 (81%) strains and serum bactericidal activity by 147 (85%) strains of Proteus and related genera. All the three i.e. serum bactericidal activity, haemolysin and haemagglutination were present in 87 (51%) strains, any two were present in 63 (37%) strains and any one was present in 34 (20%) strains.The pathogenic potential of Proteus and related species can be assessed by evaluating multiple virulence factors instead of single parameter.